The Biophysical Modelling of the Circulatory Apparatus - Vincze, Janos; Tiszay, Gabriella Vincze- (Jour Med Resh and Health Sci, 2023)
The circulatory apparatus has as a main function the constant maintaining of the internal environment in all the regions of the organism. The capillary as morphofunctional unit represents a biological membrane with selective permeability. The big circulation (systemic) starts in the left ventricle, through the aortic artery. The aortic system is made of the aortic artery and its branches, which irrigate all the tissues and organs of the human body. The blood is a liquid tissue, being formed of a fundamental substance – plasma and blood cells. The report between the plasma and figurate elements is 55:45. Excitability is the property of the heart’s muscle to respond through a contraction to certain mechanical, physical or chemical excitants. The period which includes a single contraction (systole) and a single relaxation (diastole) is called cardiac cycle. The author’s unique hypothesis is that of the circulatory apparatus in the human organism have a control system which he calls the “hypothetical secondary brain”. In the everyday regulation of the human body the functioning of these “hypothetical secondary brains” is suppressed by the regulation of the whole organism, but with tremendous probability, space-microscopy will prove the validity of this hypothesis in the near future.